Life in the Digital Trenches - Ruest, Nick; Spadoni, Carl (My University, 2009)
First on the list of the ACRL Research Committees top 10 assumptions for the future of academic libraries and librarians is that there will be an increased emphasis on digitizing collections, preserving digital archives and improving methods of data storage and retrieval. McMaster University has initiated a major digitization project, Peace and War in the 20th Century. Join us as we share our experiences in the first year of our life in the digital trenches! If you are planning a digital project be sure to bring your questions.
Keywords: digital collections; peace and war in the 20th century; drupal; pw20c; canadian heritage; Library and Information Science; Library and Information Science